Shexiang Baoxin Pill Corrects Metabolic Disorders in a Rat Model of Metabolic Syndrome by Targeting Mitochondria - Wei, Dan; Zheng, Ningning; Zheng, Lanyan; Wang, Leting; Song, Liang; Sun, Luning (Frontiers in Pharmacology, 2018)
Metabolic syndrome (MS) is a global epidemic associated with great socioeconomic and public health impact. The objective of this study was to observe the effects of Shexiang Baoxin Pill (SBP) on a MS rat model and then investigate the underlying mechanisms. Diet-induced MS model was established according to the classic formula, then the MS rats were randomly divided into two groups: control group (0.9% NaCl, 100mg/kg•d) and SBP treated group (SBP, 100mg/kg•d). The systolic blood pressure (SBP), fasting blood glucose (FBS), triglycercide (TG), high-density lipoprotein cholesterol (HDL-C), body weight and abdominal perimeter were dynamically monitored and analyzed. Serum leptin, adiponectin, TNF-α, IL-6 and IL-10 levels were measured by ELISA. The expression of leptin, adiponectin, TNF-α, IL-6 and IL-10 in adipose tissue and the expression of AMP-activated protein kinase (AMPK) and Peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α) in heart, liver, skeletal muscle and adipose tissue were measured by Western Blot; The expression of the mitochondrial protein UCP2, Cytochrome b and ATPase was observed by immunofluorescent staining.SBP could signiﬁcantly decrease serum TG, TC, LDL-C levels and increase HDL-C levels. SBP also optimized the ratio of leptin/adiponectin by decreasing the expression of leptin and increasing the expression of adiponectin in adipose tissue; SBP antagonized the inflammatory reactions by inhibiting the expression of TNF-α and IL-6, and stimulating the expression of IL-10 in adipose tissue; SBP improved the lipid metabolism by up-regulating the expression of AMPK and PGC-1α. Furthermore, SBP improved the metabolic disorder and complications of MS by adjusting the expression of several mitochondrial protein including UCP2, Cytochrome b and ATPase.SBP has prominent therapeutic effects on the metabolic syndrome, and the possible mechanisms might be related to its anti-inflammation, lipid metabolism improving, anti-oxidation and mitochondrial protective function.